Pengaruh Model Problem Based Learning Berbantuan Media Couple Card terhadap Kompetensi Pengetahuan IPAS Siswa Kelas IV - Ni Kadek Nila Dwipayani; I Gusti Agung Ayu Wulandari; D.B.Kt.Ngr Semara Putra (FONDATIA, 2023)
Learning models and media used by teachers in improving students' natural and social science knowledge competencies still use conventional learning models so that students' abilities in natural and social science learning competencies are still lacking. To overcome this, researchers suggest using varied learning models and media to improve students' natural and social science knowledge competencies. The couple card media is a paired card media that contains pictures and writings. The problem was discussed through experimental research. The results obtained from this study are the use of couple card media can improve the competence of natural and social science knowledge of fourth grade elementary school students with a total of 40 students. Data on natural and social science knowledge competencies were then analyzed with the polled variance t-test. The results of data analysis are tcount = 9.167 > ttable = 1.990 at a significance level of 5% with dk = 78, so, H0 is rejected and Ha is accepted. So, there is a significant difference in the competence of natural and social science knowledge between groups of students who are taught with a problem-based learning model assisted by media couple cards with students who are taught with conventional learning. When viewed from the average posttest value of natural and social science knowledge competence of the experimental group is 84.35 more than the control group is 70.7. It can be concluded that the problem-based learning model assisted by couple card media has an effect on the competence of natural and social science knowledge of fourth grade elementary school students.